Treatment of a Class I Malocclusion with Severe Crowding using Passive Self-Ligating Brackets - Pramustika, Agita; Widayati, Retno (UI Scholars Hub, 2020)
Presently, dental crowding is the most common problem among orthodontic patients. The prevalence of crowding in the dental arch is significantly increased in modern dentitions, and it is the most common reason why patients pursue orthodontic treatment. Objective: To report an advanced bracket systems, namely self-ligating brackets, to increase the efficacy of orthodontic treatment especially in patients with severe crowding. Case Report: A 22-year-old female patient presented with severe crowding of the maxillary and mandibular arches. In the upper arch, both second premolars were palatally positioned; in the lower arch, the lower right canine was lingually positioned and the lower left second premolar was extracted. The patient had a balanced facial profile with a straight profile and skeletal Class I relationship. Treatment was initiated using passive self-ligating brackets followed by extraction of the upper second premolars and the lower right first premolar. Conclusion: The use of passive selfligating brackets proved to be effective and resulted in a significant improvement in the patient’s dental and smile esthetics. The active treatment time was 11 months; this resulted in successfully alleviating the crowding of the maxillary and mandibular arches and significant improvement in the occlusal relationship.